Sick Tiger: Social Conflict, State–Business Relations and Exclusive Growth in Thailand. Issue 5 (20th October 2021) - Kanchoochat, Veerayooth; Aiyara, Trin; Ngamarunchot, Bank
ABSTRACT: State–business relations are considered the key to explaining long-term economic growth. However, the fact that there is neither an ideal nor convergent model of such relations requires us to explore political arrangements that underpin them. This article proposes a modified social conflict approach to state–business relations that incorporates into the analysis the role of intra-elite contestation, marginalised groups, and different kinds of leading economic actor, with a case study of Thailand. It argues that, from 1980 to 1997, Thailand's economic development occurred within the context of multifaceted conflicts and power fragmentation. Banking oligopolies played a leading role in resource allocation that took Thailand to a path of high growth, high inequality and low technological capabilities. Social conflict in the post-1997 era has shifted towards power consolidation, centring on the tussle between the traditional elite and elected politicians. Thaksin's growth regime (2001–2006) was state-led in character, with profound populist–redistributive impacts. Two military coups in 2006 and 2014 did not change this consolidated structure. The junta replaced Thaksin at the top of the pecking order and rearranged the inner–outer circles of its own clientelistic networks. This evolution of social conflict has rendered Thailand's economic development increasingly opposing to the notion of inclusive growth.